Agricultural development and land policy in VietNam - March, Sally P. (Australian Centre for International Agriculture Reasearch, 2006)
Land is a vitally important resource in Vietnam. The long-term development of Vietnamese agriculture depends on the efficient and effective use of land, and on the adoption of policies in relation to land, land markets, and associated inputs and resources. With around 75% of population still living in rural areas, the issues of land consolidation and flexibility of land use, the role of technical change and the impacts of policies related to taxes and credit will all be important.